Risk of community-acquired pneumonia in older adults with sarcopenia of a hospital from Callao, Peru 2010–2015 - Altuna-Venegas, Sofia (2019)
We are grateful to Centro de Investigacion del Envejecimiento (CIEN) of Universidad San Martin de Porres (USMP) for providing us with the database for the study. To the faculty team of research of the medical school of Universidad de Ciencias Aplicadas (UPC) for their appreciations and comments. Jorge L. Maguiña is a doctoral candidate studying Epidemiological Research at Universidad Peruana Cayetano Heredia under FONDECYT/CIENCIACTIVA scholarship EF033-235-2015 and supported by training grant D43 TW007393 awarded by the Fogarty International Center of the US National Institutes of Health .